Wireless data transfer module for leadless epicardial pacemaker - Mohammad Ikmal Mazland 1993- author 608869 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2016